2022
DOI: 10.5114/pm.2022.116402
|View full text |Cite
|
Sign up to set email alerts
|

Morphological parameters of ovarian masses and accuracy of the risk of malignancy index in diagnosing ovarian malignancy

Abstract: Introduction To detect the morphological parameters of ovarian masses and the accuracy of the risk of mali-gnancy index (RMI) in diagnosing ovarian malignancy. Material and methods 264 women in 3 groups (reproductive, premenopausal, and postmenopausal) presented with ovarian masses and scheduled for surgery were included in this study. The participants’ preoperative RMI was compared to the postoperative histology (gold standard) to detect the accuracy of RMI in diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Adilgereyeva et al . found that the RMI-I at a cut-off value > 245.7 had 87.1% sensitivity and 100% specificity in diagnosing ovarian malignancy in menopausal women [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adilgereyeva et al . found that the RMI-I at a cut-off value > 245.7 had 87.1% sensitivity and 100% specificity in diagnosing ovarian malignancy in menopausal women [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto et al found the RMI-I at a cut-off value of 450 had 75% sensitivity and 91% specificity in diagnosing ovarian malignancy [32]. Adilgereyeva et al found that the RMI-I at a cut-off value > 245.7 had 87.1% sensitivity and 100% specificity in diagnosing ovarian malignancy in menopausal women [33].…”
Section: Risk Of Malignancy Index-imentioning
confidence: 99%
“…The BMI was calculated from the studied adolescents’ body weight and their height (kg/m 2 ) [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria include adolescents < 12 years-old or >18 years-old, underweight (BMI ≤ 18.5), overweight (BMI 25–29.9) or obese (BMI > 30) [ 15 , 17 ], with irregular menstrual cycles, known medical disorders (i.e., diabetes, or hypertension), known endocrine disorders (i.e., thyroid, or hyperprolactinemia), and received exogenous hormones within the last year.…”
Section: Methodsmentioning
confidence: 99%